Determining the relationship between achievement goals and students’ anxiety in statistics course with regard to the mediating role of academic engagement - Amirgholami, Elham; Heydarei , Alireza; Askary, Parviz; Weisani, Mukhtar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and purpose: In the present study, the relationship between achievement goals and students’ anxiety in statistics course was investigated with regard to the mediating role of conflict. The present research is of the type of relational design, and more precisely, the correlation design is of the structural equation modeling type. Method: Among the first, second, third, and fourth year students, the second and fourth year students were randomly selected, and the number 324 students completed the questionnaires of this research. Finally, after removing incomplete questionnaires, 312 questionnaires were analyzed. In this research, in order to collect data, Middleton and Migli (1997) achievement goals scale, Pintrich and DeGroot (1994) academic engagement scale, and Kravis et al.’s (1985) statistics anxiety scale were used as research tools. In the present study, SPSS19 software was used for data recording and preliminary analysis, and AMOS software was used for data analysis, and a significance level of p < 0.05 was considered for all hypotheses. Findings: The fitted model shows the prediction of statistical anxiety. The numbers on the lines are standardized parameters. All paths are significant at the 0.001 level. Among the exogenous variables (mastery goals, performance goals and avoidance goals), mastery goals variable has the most direct effect on statistics anxiety. Conclusion: The findings of this research indicated that progress goals have a significant direct effect on statistics anxiety, that the effect of mastery goals and performance goals on statistics anxiety was negative and the effect of avoidance goals on statistics anxiety was positive.